Total Phenolic Content, Membrane Stabilization and Thrombolytic Activities of Corypha taliera (Arecaceae) Flowers - Chowdhury, Akhtaruzzaman; Shajib, Md Shafiullah; Tahia, Faiza; Alam, Md Ashraful; Rashid, Mohammad A (Dhaka University Journal of Pharmaceutical Sciences, 2019)
Abstract not available Dhaka Univ. J. Pharm. Sci. 18(1): 121-123, 2019 (June)